Preparation of spherical polymer powders for selective laser sintering from immiscible PA12/PEO blends with high viscosity ratios. (20th May 2019) - Yang, Xinshuang; Wei, Yang; Xi, Shuting; Huang, Yajiang; Kong, Miqiu; Li, Guangxian
Abstract: One key issue restricting the rapid application of selective laser sintering (SLS) technique is the lacking of an ideal method in preparing powder materials with good flowability and excellent sintering properties. This work demonstrates that by carefully controlling over material and processing parameters, spherical polymer powders with suitable size which meet the requirements of SLS process can be prepared from immiscible polymer blends with a large viscosity contrast by using a melt blending-extraction (MBE) method. By changing the viscosity of water-soluble poly(ethylene oxide) (PEO) matrix phase via mixing PEO with different molecular weights, the optimal viscosity ratio ( p ) for producing spherical polyamide 12 (PA12) powder with particle size ranging from 10 μm to 100 μm is determined to be about 50. In contrast, processing parameters such as mixing intensity were found to only have a marginal effect on the particle size. Available empirical or semiempirical equations based on shear flow cannot make a reasonable prediction for the particle size in such high p systems. Instead, the elongational flow presented during melt mixing is suggested to be crucial in determining the particle size. The spherical polymer powders prepared via the MBE method possess a good flowability and a wide sintering window, and can be good material candidates for the SLS technique. Graphical abstract: Image 10859913 Highlights: Spherical PA12 powder is prepared by using the melt blending-extraction method. This method involves dispersing highly viscous PA12 within a water-soluble matrix. Available equations based on shear flow cannot predict the particle size correctly. Elongational flow rather than shear flow is crucial in determining particle size. The PA12 powder prepared has good flowability and a suitable sintering window.